(untitled) - Baker, Richard E. (Boston, 2011)
The Ninth Edition of Advanced Financial Accounting is an up-to-date, comprehensive, and highly illustrated presentation of the accounting and reporting principles and procedures used in a variety of business entities. This edition continues to provide strong coverage of advanced accounting topics, with clarity of presentation and integrated coverage based on continuous case examples. The text is highly illustrated with complete presentations of worksheets, schedules, and financial statements so that students can see the development of each topic. Inclusion of all recent FASB and GASB pronouncements and the continuing deliberations of the authoritative bodies provide a current and contemporary text for students preparing for the CPA Examination and current practice. This has become especially important given the recent rapid pace of the authoritative bodies in dealing with major issues having far-reaching The book's building block approach introduces concepts with simple examples and then gradually introduces complexity, allowing students to easily keep pace with the material.
Keywords: Accounting,Kế toán